1988
DOI: 10.1016/0014-5793(88)81384-x
|View full text |Cite
|
Sign up to set email alerts
|

Right atrial dilatation increases inositol‐(1,4,5)trisphosphate accumulation Implications for the control of atrial natriuretic peptide release

Abstract: Stretching the right atrium of isolated perfused [3H]inositol-labeUed rat hearts was shown to stimulate the phosphatidylinositol turnover pathway as demonstrated by the accumulation of [3H]inositol-(1,4,5)trisphosphate and its degradation products. Stimulation was detectable after 1 min with larger increases observed after 10 or 20 min. These findings demonstrate that the myocardium can respond to dilatation by an activation of the phosphatidylinositol turnover pathway.Such a mechanism has implications for the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1989
1989
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 16 publications
(32 reference statements)
1
3
0
Order By: Relevance
“…LiCl inhibits the breakdown of Ins(1,3,4)P3 [25] {at least in the presence of Ins(1,4)P2 [26]}, but not that of Ins( 1 ,4,5)P3. The profile of release of inositol phosphates is similar to that reported previously by us in intact adult-rat heart tissue, except for the detectable peak of Ins(1,3,4)P3 at 20 min [17,27,28].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…LiCl inhibits the breakdown of Ins(1,3,4)P3 [25] {at least in the presence of Ins(1,4)P2 [26]}, but not that of Ins( 1 ,4,5)P3. The profile of release of inositol phosphates is similar to that reported previously by us in intact adult-rat heart tissue, except for the detectable peak of Ins(1,3,4)P3 at 20 min [17,27,28].…”
Section: Resultssupporting
confidence: 87%
“…This is probably a feature of the incomplete differentiation of these cells compared with the adult tissue. The pathways of inositol phosphate metabolism appear to be similar in a number of different heart preparations, isolated perfused rat heart [16,27,28], isolated guinea-pig atria [8], isolated right and left atria [7] and isolated neonatal-rat heart. This demonstrates that the absence of products of the Ins(1,4,5)P3 kinase pathway is not a feature of a particular preparation and is not related to factors such as ischaemia.…”
Section: Discussionmentioning
confidence: 99%
“…It is of interest that, in addition to preventing reperfusion arrhythmias, the aminoglycoside streptomycin has been shown to prevent arrhythmias caused by wall stress, 10 a perturbation that results in the generation of IP3. [11][12][13][14]…”
Section: Proceedings Of the Australian Physiological And Pharmacologimentioning
confidence: 99%
“…Inositol phosphates were separated using DOWEX 1 (formate) columns as described elsewhere (Woodcock et al 1987a). Analysis of the inositol mono, bis and trisphosphate fractions so obtained by anion exchange high performance liquid chromatography (HPLC) (von Harsdorf et al 1988) showed that they comprised inositol mono, bis and trisphosphate, respectively. We have previously reported the absence of products of the inositol-( 1,4,5) trisphosphate kinase pathway in rat heart (Woodcock et al 1987b;von Harsdorf et al 1989…”
Section: E T H O D Smentioning
confidence: 99%